Current ethical issues in HIV/AIDS research and HIV/AIDS care. (April 2016) - Hlongwa, P
Abstract : HIV/AIDS is a global public health concern with more than 30 million deaths having been reported. Over 70% of the 35 million people with HIV/AIDS live in sub‐Saharan Africa. The current available antiretroviral treatments are limited because they do not cure but slow the progression of disease. Therefore, care and treatment for HIV/AIDS and its related research, especially in HIV‐preventive vaccine trials, require stringent ethical guidelines because of the vulnerability of the affected individuals as it with all clinical trials. These guidelines should incorporate the basic principles in ethics which include autonomy of individuals, beneficence, non‐malfeasance and justice in the care and participation of individuals in research. With at least one in five African adults infected with the disease living in sub‐Saharan Africa, this review will discuss the current ethical issues in HIV care and HIV research based on the South African context as well as exploring some of the issues globally.